2022
DOI: 10.1556/030.2022.01849
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in elderly: Correlations of viral load, clinical course, laboratory parameters, among patients vaccinated with CoronaVac

Abstract: SARS-CoV-2 virus was initially identified in Wuhan, China, in December 2019 and a global pandemic was declared in March 2020 by World Health Organization. COVID-19 disease is characterized with severe pneumonia and hypoxemia, especially in the elderly population. The elderly population was primarily vaccinated with CoronaVac, which is a whole virion inactivated vaccine (Sinovac Biotech, China) in Turkey. This study aimed to investigate the association of viral load and laboratory parameters with the severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…And different studies included were observed for different lengths, which may result in higher incidence than prevalence. In particular, people with breakthrough infections have milder symptoms, faster recovery, shorter hospital stays, and are less likely to be infectious than primary infections which may lead to a decrease in the prevalence [ 41 – 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And different studies included were observed for different lengths, which may result in higher incidence than prevalence. In particular, people with breakthrough infections have milder symptoms, faster recovery, shorter hospital stays, and are less likely to be infectious than primary infections which may lead to a decrease in the prevalence [ 41 – 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with COVID-19 breakthrough infections have a lower viral load, shorter hospital stays, and are less likely to be infectious than primary infections [ 43 ]. While some of these breakthrough infections could lead to secondary transmissions, and indeed some of them did have high viral loads, the risk of onward transmission is reduced compared to primary infections.…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, several investigators have shown a positive relationship between older age and higher viral load and it might be as indicative for disease severity of COVID-19 in elderly. 17,18 According to these findings, the present study aimed to determine the characteristics and outcomes of vaccinated and nonvaccinated COVID-19 patients and to measure the adjusted odds ratios for poor outcomes in hospitalized patients, admitted to a tertiary hospital in Iran during the dominant Delta variant period.…”
Section: Introductionmentioning
confidence: 99%